PENGARUH METODE PENERAPAN MEDIA GRAFIS CHART PIE TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA - Mat Ali (INSPIRAMATIKA, 2020)
This research aims to increase student activities and improve student achievement by using the method of application of graphic media chart pie. Data analysis techniques using kwantitative and qualitative discrete analysis techniques. This research process is conducted in two cycles, each consisting of four stages: (1) planning, (2) implementation, (3) implementation, (4) observation and reflesi. The subjects of the study were students of grade VII B SMP Negeri 1 Sekaran Lamongan in the 2020/2021 school year numbering 25 students. The results of this study showed an increase in student activities in learning activities and also showed an increase in student achievement, thus the application of graphic media application method chart pie used in the learning of mathematics subjects operational subject fractional numbers.